2014
DOI: 10.1111/jop.12267
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of oral cancer and pre‐cancer screening programmes in Europe: a systematic review

Abstract: In order to uphold the benefits of screening, it is necessary to demonstrate an improvement in survival rates following early detection. No such randomised control trials (RCT) on OC have been undertaken in Europe. Undertaking such a RCT may be difficult in the European setting. However, the feasibility of screening for OPMDs by conventional oral examination has been demonstrated, supporting a strategy to adopt appropriate screening models, and further action from the European countries should be to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 45 publications
1
43
1
2
Order By: Relevance
“…Nonsmokers and nondrinkers visited their dentist more often, similar to previous studies [34–37]. Tumor size and lymph node status were significantly lower in group A, indicating that patients who regularly visit their dentist are treated at a lower tumor stage, as reported previously [14, 38, 39]. However, it is currently unknown if this results in lower mortality rates or improved survival rates across the population; only one high-quality randomized controlled trial supports this theory [16, 40].…”
Section: Discussionsupporting
confidence: 88%
“…Nonsmokers and nondrinkers visited their dentist more often, similar to previous studies [34–37]. Tumor size and lymph node status were significantly lower in group A, indicating that patients who regularly visit their dentist are treated at a lower tumor stage, as reported previously [14, 38, 39]. However, it is currently unknown if this results in lower mortality rates or improved survival rates across the population; only one high-quality randomized controlled trial supports this theory [16, 40].…”
Section: Discussionsupporting
confidence: 88%
“…The incidence of OCPc has declined in recent decades in most parts of the world, but has increased in the US, United Kingdom, Australia, Canada, Sweden, Denmark and the Netherlands (Chaturvedi et al, 2013). OCPc are about three times more common in men than women, but this ratio is declining mainly due to increased exposure of women to risk factors (Warnakulasuriya et al, 2015). Recent study showed an increase of the incidence of OCPc for Serbian population for both men and women between 1999 and 2010 (Videnović et al, 2016).…”
Section: Epidemiology Of Oral Cavity and Pharyngeal Cancersmentioning
confidence: 99%
“…14,15,21,22 The Cochrane collaboration and other expert consortia agree that whilst population-based annual or semi-annual screening for oral cancer is not cost-effective, targeting high-risk populations to be opportunistically screened using a visual and tactile examination should be encouraged in the primary care setting. [23][24][25][26] Opportunistic oral cancer screening by general medical practitioners (GMPs) and general dental practitioners (GDPs) should remain an integral part of the routine daily work of these groups, and particular attention should be paid to high-risk individuals. 27 In Australia the most significant risk factors for the development of oral cancer are likely to be increased age and tobacco and alcohol consumption.…”
Section: Chapter One: Introductionmentioning
confidence: 99%
“…[23][24][25][26] According to the WHO and the NIDCR, an oral cancer screening examination should include both visual and tactile components. The visual component requires examination of the face, neck, lips, labial mucosa, buccal mucosa, gingiva, floor of the mouth, tongue, and palate with mouth mirrors to help visualise all surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation